Women’s representation in higher leadership positions in Ethiopia in the last three decades since 1991 [version 2; peer review: 2 approved] - Flimon Hadaro Hando; Zeynie Chekol Degu (F1000Research)
Gender equality in decision-making positions is crucial to achieving the goals of good governance, peace, democracy, and inclusive/sustainable development. The major aim of this research article is to investigate the representation trend of women in higher decision-making positions over the last thirty years, since 1991. The federal three organs of government (law formulating, law enforcing, and law interpreting bodies) were the focus of this research. This research is a mixed type of research that inculcates both qualitative and quantitative data types. Secondary data sources from relevant government institutions were mostly used. The data was analyzed through content analysis of documents and presented via descriptive data presenting techniques. The research findings reveal that although women’s representation in positions of decision-making has advanced considerably in recent years, the empirical data throughout the previous thirty years demonstrated the underrepresentation of women in higher leadership positions within the Ethiopian federal government. Furthermore, Women never held certain higher-level government leadership positions, such as the Prime Minister position, which seems to be forbidden for women. Women made up 23%, 19%, 19%, and 24% of the House of Peoples Representatives (HPR), the House of Federation (HoF), ministerial posts, and judicial bodies, respectively over the last three decades. Women are visibly underrepresented in the executive positions as compared to others. Thus, substantial policy and practical initiatives are needed to remove institutional, social, and economic barriers to boost women’s advanced visibility in senior leadership roles.